Development of Electrochemical Oscillation Method for Identification of Prunus persica, Prunus davidiana, and Prunus armeniaca Nuts - Yan, Shuai; Yue, Yinzi; Su, Lianlin; Hao, Min; Wang, Xiaopeng; Zuo, Ting (Frontiers in Chemistry, 2020)
In this work, an electrochemical oscillation system has been developed using the Belousov–Zhabotinsky reaction. The effect of the combination of each reagent, reaction temperature, and stirring speed on the induction period, oscillating period, and oscillating life were optimized. The nuts of Prunus persica, Prunus davidiana, and Prunus armeniaca have been widely used for medical purposes. The proposed electrochemical oscillation system was then used for the identification of P. persica, P. davidiana, and P. armeniaca. Three nuts exhibited very different electrochemical oscillation profiles. The dendrogram was divided into three main principal infrageneric clades. Each cluster only contains one species, suggesting that no outlier was observed in this study. Based on the discussed results, we proposed a simple method for herbal medicine identification.